2002
DOI: 10.1107/s1600536802008231
|View full text |Cite
|
Sign up to set email alerts
|

S-Methyltrans-cis-β-N-(2-hydroxynaphthyl)methylenedithiocarbazate

Abstract: In the title compound, C13H12N2OS2, the whole mol­ecule is nearly planar. The mol­ecules are linked by N—H⋯S hydrogen bonds between the amino group and the thione S atoms, forming molecular chains along the a direction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…There are three examples, II-IV, of derivatives with a hydroxy group in the 2-position of the ring connected to the imine-C atom (Madanhire et al, 2015;Sethuraman et al, 2002;Begum et al, 2016), with their chemical diagrams shown in Scheme 2. Interestingly, there are four virtually identical molecules comprising the asymmetric unit in IV (Begum et al, 2016).…”
Section: Database Surveymentioning
confidence: 99%
“…There are three examples, II-IV, of derivatives with a hydroxy group in the 2-position of the ring connected to the imine-C atom (Madanhire et al, 2015;Sethuraman et al, 2002;Begum et al, 2016), with their chemical diagrams shown in Scheme 2. Interestingly, there are four virtually identical molecules comprising the asymmetric unit in IV (Begum et al, 2016).…”
Section: Database Surveymentioning
confidence: 99%